A Case of Drug Reaction with Eosinophilia and Systemic Symptoms. (27th August 2012) - Kellett, Sally; Cock, Charles
Abstract : Drug reaction with eosinophilia and systemic symptoms (DRESS) is characterized by fever, skin rash, hematological abnormalities, and systemic involvement such as hepatitis. DRESS usually presents 2–6 weeks after drug initiation. DRESS should be suspected on clinical grounds in the setting of the introduction of new drug therapy and is most commonly described after the introduction of aromatic anticonvulsants, allopurinol, or antiretroviral therapies. We describe here a case of DRESS due to phenytoin exposure with complete resolution on drug discontinuation. Our patient developed DRESS with a skin rash, lymphadenopathy, and markedly abnormal liver enzymes, 4 weeks after drug initiation following drainage of a brain abscess. He was initially diagnosed as having a recurrence of the abscess or sepsis of another origin. It is important to recognise the possibility of DRESS in this setting, as a good outcome depends on the immediate withdrawal of the offending drug. A mortality rate of up to 10% has been described in unrecognised cases.